Respuesta :

First split up the equation.

(-5×7) + (9 × 5/5)

We know that 5/5 is equal to 1, so replace 5/5 with 1.

(-5×7) + (9 × 1)

Now solve the first part. (Remember, a negative times a positive is always a negative)

-5 × 7 = -35

Now solve the second part.

9 × 1 = 9

Add.

(-35 + 9 equals the same as 35 - 9, but negative)

-35 + 9 = -26

-5 × 7 + 9 × 5/5 = -26

Wolfyy

Remember to use PEMDAS when solving.

= −5 × 7 + 9 × 5 / 5

= -35 + 45/5

= -35 + 9

= -26

Best of Luck!

ACCESS MORE